Dissolving microneedles for long-term storage and transdermal delivery of extracellular vesicles. (August 2022) - Bui, Van Dat; Son, Soyoung; Xavier, Wilbin; Nguyen, Van Quy; Jung, Jae Min; Lee, Jungmi; Shin, Sol; Um, Wooram; An, Jae Yoon; Kim, Chan Ho; Song, Yeari; Li, Yuce; et al.
Abstract: Extracellular vesicles (EVs) have shown great potential in disease diagnosis and treatment; however, their clinical applications remain challenging due to their unsatisfactory long-term stability and the lack of effective delivery strategies. In this study, we prepared human adipose stem cell-derived EV (hASC-EV)-loaded hyaluronic acid dissolving microneedles (EV@MN) to investigate the feasibility of EVs for their clinical applications. The biological activities of the EVs in this formulation were maintained for more than six months under mild storage conditions, especially at temperatures lower than 4 °C. Moreover, the EV@MN enabled precise and convenient intradermal delivery for sustained release of EVs in the dermis layer. Therefore, EV@MN significantly improved the biological functions of hASC-EVs on dermal fibroblasts by promoting syntheses of proteins for the extracellular matrix such as collagen and elastin, enhancing fibroblast proliferation, and regulating the phenotype of fibroblast, compared with other administration methods. This research revealed a possible and feasible formulation for the clinical application of EVs.